2020
DOI: 10.1177/1357633x20940142
|View full text |Cite
|
Sign up to set email alerts
|

Primary-care registered nurse telehealth policy implications

Abstract: Coronavirus disease 2019 (COVID-19) has drastically changed health-care delivery models within primary-care settings. Primary-care providers are limiting routine care face-to-face office visits while triaging COVID-19 symptomatic patients to hospital emergency rooms. Primary-care providers are rapidly adopting telehealth modalities for care provisions during this unprecedented pandemic to allow practices to continue delivering primary care while preventing community spread of COVID-19. Federal legislation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 12 publications
1
23
0
6
Order By: Relevance
“…During the period from March to April 2020, when telehealth was funded for GPs and allied health but not for GPNs, 25 the role of the nurse was significantly constrained. A similar story was reported by Watkins and Neubrander, 26 who describe how American nurses were prohibited from providing reimbursable telehealth services. The impact of funding models limiting GPN roles in Australia is not new 27 ; however, the impact seen during COVID-19 highlights the need for funding to support rather than inhibit health professionals to work to the full extent of their scope of practice to optimise service delivery during crises.…”
Section: Discussionsupporting
confidence: 64%
“…During the period from March to April 2020, when telehealth was funded for GPs and allied health but not for GPNs, 25 the role of the nurse was significantly constrained. A similar story was reported by Watkins and Neubrander, 26 who describe how American nurses were prohibited from providing reimbursable telehealth services. The impact of funding models limiting GPN roles in Australia is not new 27 ; however, the impact seen during COVID-19 highlights the need for funding to support rather than inhibit health professionals to work to the full extent of their scope of practice to optimise service delivery during crises.…”
Section: Discussionsupporting
confidence: 64%
“…Nurses have been described as the linchpin of healthcare systems and have played a central role in the COVID‐19 (Watkins & Neubrander, 2020). The value of telehealth nursing practice has been increasingly recognised in the United States, and a clear evidence base suggests that it may be as effective as face‐to‐face visits (Speyer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, virtual transitional care and chronic disease management visits by RNs are reimbursable by the Centers for Medicare and Medicaid Services. However, the recent legislation that has expanded healthcare reimbursement for telehealth during the pandemic neglected to include RNs as eligible providers (Watkins & Neubrander, 2020). Our programme provides further evidence that experienced RNs can work assume more responsibility than is currently promoted by reimbursement practices while remaining within their scope.…”
Section: Discussionmentioning
confidence: 99%
“…Telenursing findings will be fruitful in improving nursing services in particular and or health services in general. Telehealth nursing practice utilized technology-based communication to provide remote patient nursing services such as assessment, providing educational interventions, monitoring and evaluating patient care (23). Another study showed that nurses were satisfied with facilitating patient data on a primary PC or personal tablet to be able to monitor intravenous fluids as well as some drugs that could be monitored from outside the patient's room (24).…”
Section: Discussionmentioning
confidence: 99%